Surveys on Reproduction Status and Calf Production of Hanwoo Farmers - Byoung-Chul Yang; Sung-Sik Kang; Ui-Hyung Kim; Jang Sun-Sik; Boh-Suk Yang; Seok-Dong Lee; Sang-Rae Cho (The Korean Society of Animal Reproduction and Biotechnology, 2017)
This study was conducted to investigate the breeding status of farms to improve the production efficiency of Hanwoo calf. The study was conducted on 45 farms divided into two groups. This study was conducted to investigate the breeding size and breeding area of Hanwoo cows. The average age at first delivery of Hanwoo was 28.7 months. The number of artificial insemination per pregnancy was 1.45±0.32, and the number of artificial insemination days after birth was 119.8 days. Conception rates were 75.2±16.93% for small farms and 70.6±17.46% for medium sized farms and 71.4±11.03% for large farms. When we looked at farming methods, 'the farmers using estrus observation aids' had 10.42% higher calf production rate than the 'unused farmers'. The farms vaccinated with IBR and BVDV for breeding cattle showed a 4.41% decrease in abortion, stillbirth and mortality. According to farming conditions, conception rate and delivery rate improved by 3.47% and 18.29%, respectively, when grazing and exercising were performed. Observation, immunization and grazing were found to be important indicators for improving calf production efficiency in Hanwoo farm. This study can be used as a research data to improve the reproductive rate of farmhouse sites through the survey on the breeding status of Hanwoo farmers.